Effect of origin, temperature, and roasting time on the volatile compounds of arabica coffee (Coffea arabica) a meta-analysis study - Belgis, Maria; Azizah, Amalia Nur; Afandi, Frendy A.; Taruna, Iwan; Witono, Yuli; Susanti, Siti (2025)
Several studies have assessed how origin and roasting conditions, encompassing both temperature and length of roasting, shape the volatile composition that defines arabica coffee’s sensory attributes. However, methodological differences among these studies have often led to inconsistent or even conflicting conclusions. For example, coffee grown in different regions tends to produce distinct volatile compound profiles. This study applied a meta-analysis to systematically evaluate and compare findings, providing a more reliable overview of how geographical origin and roasting parameters affect volatile compounds. To address this, a meta-analysis was performed to derive more conclusive insights into the influence of these factors on key volatile compounds in arabica coffee. This study focuses on evaluating the influence of origin, roasting temperature, and roasting time on major volatile compounds that shape the distinctive aroma of arabica coffee. The analyzed compounds represent the dominant volatile compounds typically found in coffee beans, particularly from the pyrazine, furan, and pyridine groups. The analysis focused on a group of dominant volatiles – namely pyridine, 2-methylpyrazine, two dimethylpyrazine isomers (2,5- and 2,6-), in addition to 2-ethyl-6-methylpyrazine, 2-ethyl-5-methylpyrazine, and furfural. Roasting was classified into three categories: light, medium, and dark. Volatile compound
profiles were largely shaped by the geographical origin of the beans, underscoring their critical role in aroma development. Arabica beans sourced from Nicaragua and Ethiopia yielded the greatest concentrations, with Indonesian samples ranking lower in comparison. When subjected to light roasting, increased levels of pyrazine (2,5-dimethyl-; 2-ethyl-5-methyl-) and furfural were identified. Medium roasting yielded the greatest amount of 2-ethyl-6-methylpyrazine, whereas dark roasting was characterized by elevated levels of pyridine, 2-methylpyrazine, and 2-ethyl6-methylpyrazine. Differences in volatile compounds at varying roast levels establish the unique aroma identity of arabica coffee and directly influence consumer judgments of flavor quality.
Keywords: Arabica coffee; Roasting (Cooking); Coffee roasting industry